A strategy for effective recovery of salvianolic acid a from Salvia miltiorrhiza (Danshen) through multiple interactions. (15th February 2022) - Qian, Jun; Xu, Xiaoqian; Su, Jiajia; Zeng, Weihuan; Han, Bing; Hao, Xiaolong; Kai, Guoyin
Abstract: Salvianolic acid A (SAA) has high pharmacological activity and is widely used in the treatment of various diseases. We reported herein a strategy for effective adsorption of SAA from aqueous solution by surface molecularly imprinted magnetic nanoparticle (SIMNP). 4-(acryloyloxy)phenylboronic acid, 1-vinylimidazole and methacrylamido propyl trimethyl ammonium chloride were chosen as functional monomers. 1-vinylimidazole not only neutralizes the acidity of SAA solution to help phenylboronic acid react with ortho-phenolic hydroxyl groups of SAA quickly and stably, but also captures SAA through electrostatic interaction and hydrogen bond. Besides, the introduction of positively charged methacrylamido propyl trimethyl ammonium chloride can accelerate the adsorption kinetics. Adsorption kinetically follows a pseudo-second-order model and achieves equilibrium within 10 min at 298.15 K with high selectivity. And the maximum adsorption capacity can be determined to be 1117.6 mg/g by Langmuir adsorption model. Adsorption mechanism involves the formation of covalent bond, electrostatic interaction and hydrogen bond. This work indicates that SIMNP is a promising adsorbent to realize effective capture of SAA from aqueous solution.